In vitro screening of fungal endophytes from sandalwood (Santalum album) as antagonists to phytopathogens - AGNES V. SIMAMORA; MAYAVIRA V. HAHULY; PETRONELLA S. NENOTEK; YENNY RAJA KANA; M. KASIM; RODDIALEK POLLO; ANTONIUS R. B. OLA; FADLAN PRAMATANA (Society for Indonesian Biodiversity, 2024)
Abstract. Simamora AV, Hahuly MV, Nenotek PS, Kana YR, Kasim M, Pollo R, Ola AR, Pramatana F. 2024. In vitro screening of fungal endophytes from sandalwood (Santalum album) as antagonists to phytopathogens. Biodiversitas 25: 361-371. Endophytic fungi possess bioactive compounds and generate secondary metabolites like their host plants. The phytochemical compounds found in sandalwood plants (Santalum album L.) are recognized for their anti-pathogenic properties, suggesting the potential of sandalwood endophytic fungi as effective anti-phytopathogens. Alternaria solani and Fusarium oxysporum threaten tomato plants, whereas Phytophthora palmivora is particularly detrimental to cocoa plants. The aims of this study were: (i) to obtain isolates of endophytic fungi from roots, stems, and leaves of sandalwood plants and (ii) to assess the ability of endophytic fungi as anti-phytopathogens in vitro. Endophytic fungi were isolated through a direct plating method and next by purification and identification. All obtained endophytic fungi underwent testing for their antagonistic potential against A. solani, F. oxysporum, and P. palmivora in vitro through the dual culture method. The inhibition percentage was analyzed using variance analysis and further examined with the 5% HSD test. The study successfully isolated 104 endophytic fungal isolates from the sandalwood; 29 isolates were from the roots, 33 from the stems, and 42 from the leaves. All endophytic isolates demonstrated the ability to inhibit the growth of A. solani, F. oxysporum, and P. palmivora in vitro, with various inhibition percentages ranging from 26.7 to 83.3%. Further research will concentrate on secondary metabolites from selected isolates showing inhibition levels exceeding 70%.